Hubungan Kemampuan Mobilisasi dengan Risiko Jatuh pada Lansia Hipertensi - Sinta Kholifah Mar'ah Konitatillah; Latifa Aini Susumaningrum; Hanny Rasni; Tantut Susanto; Roro Dewi (Jurnal Keperawatan, 2021)
Hypertensive elderly influences body balance that affects their ability to mobilize. Therefore, this condition can improve a risk for falling. The aimed of this study was to analyzed the relationship between mobilization ability and risk for fall among elderly with hypertension in Tresna Werdha Social Services (PSTW) Bondowoso. A cross sectional design was conducted among 47 elderly using total sampling. A self-administered questionnaire was used to measure sociodemographic of elderly, while Elderly Mobility Scale (EMS) was performed to measure mobilization ability and Morse Falls Scale was performed to measure risk for fall. The relationship mobilization ability and risk for fall was analysed using Chi Square test. The result showed that among 47 elderly were 49,8% of independent and 46,8% of low risk for falling. There were significantly relationship between mobilization ability and risk for fall (X2 = 14,674; p = 0.001). The conclusion of this study, there is a relationship between mobilization ability and risk of fall among elderly. Therefore, elderly should be active in physical activities to reduce the risk of falling.